Doctor, There's a Tadpole in my Feces!. Issue 3 (1st June 2006) - Drisdelle, Rosemary; Forward, Kevin R
Abstract : A 36-year-old male resident of a coastal Nova Scotia community presented to his family physician after he noted moving objects in his feces (Figure 1). Although concerned and revolted, he was asymptomatic. He was worried that the organisms were an intestinal parasite he had passed in his stool. The organisms were approximately 2.5 cm long and resembled tadpoles. The fecal sample was sent to the Parasitology Section at the Queen Elizabeth II Health Sciences Centre in Halifax, Nova Scotia, for identification.